The Prevalence of Attention Deficit Hyperactivity Disorder, Internet Gaming Disorder and Their Association Among Adults in Jordan: A Cross-Sectional Study - Kaffaf, Ahmad; Attarri, Ahmed; Abdulelah, Hussein; Barakat, Tamer; Omar, Yousef (Jordan Medical Journal, 2025)
Objective: This study investigates the prevalence of adult ADHD and Internet Gaming Disorder (IGD) among Jordanian students and graduates and examines their associations and determinants. Method: A cross-sectional study was conducted using an online self-administered questionnaire comprising three sections: demographics, the Adult ADHD Self-Report Scale (ASRS), and an IGD assessment. Results: Among 1989 participants, 25.6% screened positive for adult ADHD (average ASRS score: 7.25). Factors associated with Adult ADHD included male gender, younger age, lower GPA, and prior psychiatric diagnoses. Additionally, 14.7% met IGD criteria. Male gender, younger age, single marital status, and southern Jordan residence were significantly associated with risky gaming behavior and IGD. A significant connection between IGD and ADHD was observed. Conclusion: This study underscores a significant prevalence of adult ADHD and IGD, emphasizing the need for heightened awareness and intervention strategies to address the psychological implications on individuals’ well-being.